A vacuolar hexose transport is required for xylem development in the inflorescence stem. Issue 2 (22nd November 2021) - Aubry, Emilie; Hoffmann, Beate; Vilaine, Françoise; Gilard, Françoise; Klemens, Patrick A W; Guérard, Florence; Gakière, Bertrand; Neuhaus, H Ekkehard; Bellini, Catherine; Dinant, Sylvie; Le Hir, Rozenn
Abstract: In Angiosperms, the development of the vascular system is controlled by a complex network of transcription factors. However, how nutrient availability in the vascular cells affects their development remains to be addressed. At the cellular level, cytosolic sugar availability is regulated mainly by sugar exchanges at the tonoplast through active and/or facilitated transport. In Arabidopsis ( Arabidopsis thaliana ), among the genes encoding tonoplastic transporters, SUGAR WILL EVENTUALLY BE EXPORTED TRANSPORTER 16 ( SWEET16 ) and SWEET17 expression has been previously detected in the vascular system. Here, using a reverse genetics approach, we propose that sugar exchanges at the tonoplast, regulated by SWEET16, are important for xylem cell division as revealed in particular by the decreased number of xylem cells in the swt16 mutant and the accumulation of SWEET16 at the procambium–xylem boundary. In addition, we demonstrate that transport of hexoses mediated by SWEET16 and/or SWEET17 is required to sustain the formation of the xylem secondary cell wall. This result is in line with a defect in the xylem cell wall composition as measured by Fourier-transformed infrared spectroscopy in the swt16swt17 double mutant and by upregulation of several genes involved in secondary cell wall synthesis. Our work therefore supports a model in which xylem development partially depends on the exchange of hexoses at the tonoplast of xylem-forming cells. Abstract : ylem development and secondary cell wall formation partially depend on the control of cytosolic sugar availability, which is regulated by tonoplastic sugar transporters.